Precarity aspects during the startup process. A qualitative analysis of uncertainty while founding a business at the example of Czech early-stage startups. - Bogdanov, Peter; Lukeš, Martin, 1976-; Bočková, Nina, 1971-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This master thesis focuses on the topic of precarity and how early-stage start-up founders in the Czech Republic are dealing with uncertainty during the start-up process. First, the underlying problem of precarity is defined and put into the context of start-up founders in the Czech ecosystem. Next, theoretical frameworks connected to the research topic as well as the methodology connected to the data collection via semi-structured qualitative interviews is described. In the practical part of the thesis the findings of the interviews are discussed. While using a mix of deductive and inductive coding for the qualitative analysis, nine dimensions of precarity for early-stage start-up founders in the Czech Republic have been identified. Finally, after evaluating the findings, normative recommendations for founders dealing with uncertainty and precarity are obtained.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses